Acute mastoiditis in children - Cassano, Pasquale; Ciprandi, Giorgio; Passali, Desiderio (Acta Biomedica Atenei Parmensis, 2020)
Acute mastoiditis is the most common complication of acute otitis media. Although rare, the disease is carefully studied by otolaryngologists because it usually affects very young children with severe clinical course and sometimes causes serious complications. Most important risk factors are the young age (often>2 years), high fever, alteration of the laboratory findings (very high values of WBC count, absolute neutrophil count and C-reactive protein), while less important are previous antibiotic therapy or previous middle ear infections. The main pathogen of the acute mastoiditis is Streptococcus pneumoniae, followed by Streptococcus piogenes, Haemophilus influentiae, and Staphylococcus aureus. The finding of Pseudomonas aeruginosa is not uncommon, but often its presence is often considered a contamination or simultaneous infection. The complications can be extracranial (subperiosteal abscess, Bezold’s abscess); intratemporal (facial nerve palsy, labyrinthitis) and intracranial (subdural abscess). The complications have often a very serious clinical course and potentially life-threatening. Antibiotic therapy is the main treatment in not complicated forms. Considering the prevalence of Streptococcus pneumoniae, cephalosporins are the antibiotic of choice, but they have to be administrated intravenously in hospitalized patients. Combinations with other antibiotic are suggested when multibacterial flora is present. In complicated forms of acute mastoiditis, the antibiotic treatment can be particularly important, in combination with other specific drugs (i.e. anticoagulants and/or corticosteroids). Surgical treatments, such as incision of abscesses, mastoidectomy, and neurosurgical procedures, are sometimes performed in combination with medical therapy in very severe complications. Data from our experience are briefly reported